2023
DOI: 10.1111/jerd.13017
|View full text |Cite
|
Sign up to set email alerts
|

Color stability of bulk‐fill compared to conventional resin‐based composites: A scoping review

Abstract: Objectives: To conduct a scoping review on color stability of bulk-fill compared to conventional resin-based composites exposed to colored beverages. Materials and Methods:In vitro studies, investigating bulk-fill resin-based composites color stability submitted to artificial staining by colored beverages were included.Studies investigating color change induced by smoke and whitening treatments as well as papers not written in English language were excluded. A systematic search, following the Preferred Reporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…36 The same study demonstrated that the solubility of RXU was comparable to, or lower, than the other investigated cements. Since water sorption is related to color stability of resin-based materials, 38 these findings are in accordance with the results of another recent study on the color stability of resin cements. 39 This group of authors found that the color stability of RXU was comparable to Panavia SA and lower than Panavia V5…”
Section: Physical Properties Of Universal Cementssupporting
confidence: 92%
See 2 more Smart Citations
“…36 The same study demonstrated that the solubility of RXU was comparable to, or lower, than the other investigated cements. Since water sorption is related to color stability of resin-based materials, 38 these findings are in accordance with the results of another recent study on the color stability of resin cements. 39 This group of authors found that the color stability of RXU was comparable to Panavia SA and lower than Panavia V5…”
Section: Physical Properties Of Universal Cementssupporting
confidence: 92%
“…This could be due to differences in the composition of the resin matrix and filler content and size. 38 Polymerization stress to feldspathic ceramics of SOC compared to 8 different self-adhesive cements (all employed after a silane…”
Section: Physical Properties Of Universal Cementsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 These alterations promote a change in surface smoothness, loss of gloss, and color change because the surface roughness also interferes directly with the intensity and rate of pigmentation. 13 - 14 This is why it is imperative to assess the characteristics of these toothpastes and their effect on restorative materials.…”
Section: Introductionmentioning
confidence: 99%
“…Color stability is a crucial property of restorative materials, and color can be modified by intrinsic and extrinsic discolorations. 5 , 13 Intrinsic factors are associated with material degradation due to components such as organic matrix composition and the initiator system, whereas the size, content, and hardness of the filler particles are directly influenced by photopolymerization. 14 - 15 Extrinsic factors are associated with pigment adsorption and absorption derived from sources such as nicotine, medications, and the patient’s diet.…”
Section: Introductionmentioning
confidence: 99%